Analisis Kinerja Pemerintah Negeri dalam Pembangunan di Negeri Wahai - Sauban Sabban; Victor Sanjak Ruhunlela; Muhammad Alfa Sikar (Lembaga Intelektual Muda (LIM) Maluku, 2023)
This study aims to determine the performance of the state government in development in Wahai Country, North Seram District. The type of research used in this research process uses qualitative descriptive research. The population in this study is the entire government apparatus of Wahai State, North Seram District. Respondents in this study amounted to 6 people who were part of the Wahai State Government. The data collection techniques used are observation and interviews. Data analysis techniques used in this study are data reduction, data presentation, and conclusions. The results showed that the development implementation process is based on the RJPMDes that has been prepared and agreed upon together, by optimizing the implementation time well. In realizing the aspirations of the community, it is first discussed in a joint meeting and agreed upon then used as a development goal through the determination in the RJPMDes. To ensure the implementation of state government policies, there must be a mechanism that is used and becomes a reference in the running of a development activity. The State Government also has the obligation to provide reports on Infrastructure Development in the country, to the Regent through the sub-district and, provide accountability reports to BPD